Thinking Seriously About Gangs: Towards a Critical Realist Approach - Andell, Paul (Springer eBooks Law and Criminology, 2019)
1. Realism, Street Culture and a Border Clash -- 2. Realist Methodology and Motivation -- 3. Policy Denial and New Gang Cities -- 4. Policy Blame: ‘Addressing Gangs in Austere Times’ -- 5. Drivers and Contingencies of Gang Policy Formulation 1: Gangs Call-ins and Policy Transfer -- 6. Drivers and Contingencies of Gang Policy Formulation 2: ‘Bedazzled’-Think Tanks and the Media -- 7. Towards a Critical Realism of Gangs -- 8. Conclusion